Molteno3 Implantation as Primary Glaucoma Surgery - Juha O. Välimäki; Ari-Pekka A. Ylilehto (Journal of Ophthalmology)
Purpose. To determine the outcome of Molteno3 implantation as primary glaucoma surgery and to analyze the factors influencing the surgical outcome. Methods. This is a retrospective clinical study of 106 consecutive eyes (97 patients) with no previous glaucoma surgery. Surgical failure was defined as an IOP > 21 mmHg or less than a 20% reduction below baseline, or IOP ≤ 5 mmHg, on two consecutive visits after 3 months follow-up, or reoperation for glaucoma or loss of light perception. Results. At the end of the follow-up (mean, 35 months; range, 12–71 months), the mean postoperative IOP (14.2 ± 4.4 mmHg) was statistically significantly lower than the preoperative IOP (35.2 ± 9.7 mmHg) (P<0.001). Life-table success rates were 97%, 94%, and 91% after follow-up of 12, 24, and 36 months, respectively. Success rate for an IOP ≤ 18 mmHg was 77% at the last visit. Success was not influenced by previous cataract surgery, sex, age, laser trabeculoplasty (LTP), preoperative IOP, or number of antiglaucoma medications. Forty-seven eyes had 66 postoperative complications. Conclusions. The primary Molteno3 implant provided significant IOP lowering with minimal and manageable complications in uncontrolled glaucoma. Neither previous cataract surgery nor LTP had any detrimental effect on surgical success.